The Place and Role of Visual Media in the Creation of Speech - Nabieva Zarrina Isomiddinovna (International Journal on Orange Technologies, 2021)
This article analyzes the visual and emotional means of language that are formed in the speech of a person with his internal emotions. A person during communication with people releases from himself a different emotional category associated with his inner world and displayed in contexts and transmitted to the rest of the communication members